Center-Pivot-Irrigated Popcorn Cost-Return Budget - Sartwelle III, James D.; Henson, Darl W. (My University, 1997)
This publication outlines the expected costs and returns for center-pivot-irrigated popcorn in Kansas.
MF996_1997_10
Keywords: MF996; Economics; Crops; MF